Clinical evaluation of GEM 21S® and a collagen membrane with a coronally advanced flap as a root coverage procedure in the treatment of gingival recession defects: A comparative study - Preetinder Singh; D K Suresh (Wolters Kluwer Medknow Publications, 2012)
Aim: Clinical evaluation of efficacy of rhPDGF-BB plus beta tricalcium phosphate (GEM 21S ® ) along with a collagen membrane in root coverage using a coronally advanced flap. Materials and Methods: This human case series evaluated the clinical outcome of rhPDGF-BB with beta-tricalcium phosphate (GEM 21S®) and a collagen membrane in the treatment of recession defects using a coronally advanced flap. Patients were followed postoperatively, and healing was evaluated at 1, 3, and 6 months, with recession depth as the primary outcome measure. Results : This pioneer case series revealed a favorable tissue response to GEM 21S® and collagen membrane from both clinical and esthetic point of view in regenerative periodontal surgery.